How liquidity, profitability, and leverage ratios influence financial distress: A study on Indonesian mining firms - Arifuddin Arifuddin; Erwin Hadisantoso; Ika Maya Sari; Annisa Fitrah Yulianti (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
This study investigates the impact of liquidity, profitability, and leverage ratios on financial distress in mining companies listed on the Indonesia Stock Exchange. It posits that higher liquidity in a company correlates with reduced financial distress. The research encompasses eight mining companies observed from 2016 to 2020. Purposive sampling was employed to select a sample of eight companies meeting specific criteria. The study utilizes multiple linear regression analysis as its analytical approach. The findings, significant at the 5% level, reveal that liquidity, profitability, and leverage ratios collectively exert a substantial influence on financial distress, accounting for 85.3% of the variance in the dependent variable. Specifically, the study concludes that: 1) Liquidity has a significant negative effect on financial distress, 2) Profitability also demonstrates a significant negative impact on financial distress, and 3) Leverage exhibits a significant positive effect on financial distress.